2023
DOI: 10.3389/fnagi.2023.1207012
|View full text |Cite
|
Sign up to set email alerts
|

Three potential neurovascular pathways driving the benefits of mindfulness meditation for older adults

Abstract: Mindfulness meditation has been shown to be beneficial for a range of different health conditions, impacts brain function and structure relatively quickly, and has shown promise with aging samples. Functional magnetic resonance imaging metrics provide insight into neurovascular health which plays a key role in both normal and pathological aging processes. Experimental mindfulness meditation studies that included functional magnetic resonance metrics as an outcome measure may point to potential neurovascular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 136 publications
0
1
0
Order By: Relevance
“…At variance with extensive research on various types of non-religious meditation practices such as, for example, mindfulness (Pommy et al, 2023), research on the neural correlates of religious chanting is in its early stages. An observational study performed in 2019, showed that the functional effects of religious chanting are not due to changes of peripheral cardiac or respiratory activity, nor to implicit language processing.…”
Section: Religious Chanting a Practice Different From All Othersmentioning
confidence: 99%
“…At variance with extensive research on various types of non-religious meditation practices such as, for example, mindfulness (Pommy et al, 2023), research on the neural correlates of religious chanting is in its early stages. An observational study performed in 2019, showed that the functional effects of religious chanting are not due to changes of peripheral cardiac or respiratory activity, nor to implicit language processing.…”
Section: Religious Chanting a Practice Different From All Othersmentioning
confidence: 99%